(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we deal with the following fully nonlinear partial differential equation of parabolic type F(x, t, u,Du,D²u) + u_t = 0 in Q_T with the third boundary value conditions. We prove that under some structure conditions on F, the W^2,1_p (p > 3N + 1) strong solutions for the problem have the ^1,0_∞ a priori estimates.